Wisconsin's Progressive Tradition and a Century of Reform - Feingold, Russ (My University, 2009)
Video of U.S. Senator Russ Feingold delivering the 2009 Fromkin Lecture, "Wisconsin's Progressive Tradition and a Century of Reform". Also included is a poster advertising the event.
Keywords: Reform; Progressives; Wisconsin; Feingold; Fromkin